2014
DOI: 10.1371/journal.pone.0091340
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Age-Related Differences in Chronic Disease Management in a Population-Based Cohort Study: A New Paradigm of Primary Care Is Required

Abstract: BackgroundOur interest in chronic conditions is due to the fact that, worldwide, chronic diseases have overtaken infectious diseases as the leading cause of death and disability, so their management represents an important challenge for health systems. The aim of this study was to compare the performance of primary health care services in managing diabetes, congestive heart failure (CHF) and coronary heart disease (CHD), by age group.MethodsThis population-based retrospective cohort study was conducted in Ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Creative solutions are needed to address the escalating health care burden of chronic diseases. Adopting evidence-based approaches for the management of chronic conditions such as CHF can make health care systems more coherent and efficient, and provide a way to improve quality of care across a range of chronic health problems, as well as ensuring that primary care really is a service that comes as close as possible to where people live and work, with a level of care that guarantees fewer health disparities across population subgroups [ 3 ]. More action is still needed to promote a proactive, integrated approach to chronic care capable of actively involving chronically ill patients in all seasons of their life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creative solutions are needed to address the escalating health care burden of chronic diseases. Adopting evidence-based approaches for the management of chronic conditions such as CHF can make health care systems more coherent and efficient, and provide a way to improve quality of care across a range of chronic health problems, as well as ensuring that primary care really is a service that comes as close as possible to where people live and work, with a level of care that guarantees fewer health disparities across population subgroups [ 3 ]. More action is still needed to promote a proactive, integrated approach to chronic care capable of actively involving chronically ill patients in all seasons of their life.…”
Section: Discussionmentioning
confidence: 99%
“…It is also essential to analyze the determinants of adherence in order to identify population groups likely to be scarcely compliant with disease management programs. Adherence to appropriate chronic disease management programs is a multifaceted issue influenced by how health care is delivered and by patient-related factors (called antecedents ) that may have an impact on an individual’s propensity to follow medical recommendations; some sociodemographic factors are among these antecedents [ 3 ]. Several studies have shown that age, ethnicity and formal education have an important influence on adherence to health professionals’ advice [ 4 , 5 ], for instance.…”
Section: Introductionmentioning
confidence: 99%
“…The regional dataset of this population contains information about gender, age, and chosen general practitioners (GP) at January 1 st , 2011. This dataset also informs about the participation of patients' GPs to the regional chronic care model project (CCM), launched by Tuscany Region during year 2010, and concerning the commitment for a more proactive behavior by family physicians regarding current care policy of major chronic diseases …”
Section: Methodsmentioning
confidence: 99%
“…GPs to the regional chronic care model project (CCM), launched by Tuscany Region during year 2010, and concerning the commitment for a more proactive behavior by family physicians regarding current care policy of major chronic diseases. 22 From a different database we identified as diabetic each individual who had at least 1 hospitalization with main or concomitant diagnosis of diabetes (ICD9-CM 250*), or who had an active exemption for diabetes, or had at least 2 prescriptions of antidiabetic drugs in a year, before January 1 st 2011. 23 In order to avoid possible selection biases, those with a new diagnosis of diabetes satisfying at least one of these conditions after January 1 st , 2011, along with those who had chosen a GP joining the CCM program after year 2011, were dropped from the cohort.…”
Section: This Dataset Also Informs About the Participation Of Patients'mentioning
confidence: 99%
“…Currently, it covers a population of about 9 million subjects living in some of the Local Health Authorities in 9 of the 21 regional health care systems in the country. Studies completed so far using data from this network were aimed at evaluating the quality and equity of primary care, the impact of policies in this field [Visca2013, 44 , 45 , 46 , 47 and methodological challenges of such studies [Gini2014]. 48 , 49 The network currently participates in several studies funded by the Italian Ministry of Health.…”
Section: Methodsmentioning
confidence: 99%